8z-7=9z-4

Simple and best practice solution for 8z-7=9z-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8z-7=9z-4 equation:



8z-7=9z-4
We move all terms to the left:
8z-7-(9z-4)=0
We get rid of parentheses
8z-9z+4-7=0
We add all the numbers together, and all the variables
-1z-3=0
We move all terms containing z to the left, all other terms to the right
-z=3
z=3/-1
z=-3

See similar equations:

| 1/4+b/9=17 | | 7(x-4)=x+5 | | 3x+1-x=4+x+9 | | k2+6k+1=8 | | -5x-9=31 | | 4c+9=2c+15 | | 5x^2+240=0 | | 0.5t+49.95=90.20 | | 0.033=0.07x | | 6x+27=3x-36 | | 2/6-7n/12=1/6 | | 3/10y-3=y/5+5 | | -2r+3r=4(4r-5)+7(r+6) | | x0.033=0.07 | | 7^-8n=77 | | (3x+)x=24 | | 16/3=4u | | -3x+4x=-408+x | | -2(-7y+8)-2y=2(y-2)-6 | | 3(2a)^2=0 | | y+4(-1)=11 | | 0.1t+29.95=0.5t+49.95 | | 10.3=0.6/y | | 5(2x-39)=6x+14 | | 7x+1x-5=2(4x+9) | | -6(9x+5)=-3x+4x=-408+x | | r2+9r+18=0 | | -6(9x+5)=-3x+4x | | 7x=4x=18 | | C=8/3(k-86) | | (g+15)^2=g^2+3g+2.25 | | 6(6-4n)+4(3+5n)=7-4n+1-5n |

Equations solver categories